إجراءات الإخطار والإحالة أمام المحكمة الدستورية - بالمسعود ،آمال; مسيوغي، مروان; سلطاني ،عبد العالي (جامعة الوادي University of El Oued, 2024)
قصد ممارسة صلاحياتها الدستورية تحتاج المحكمة الدستورية إلى تدخل بعض الجهات حددها المؤسس الدستوري، ويكون التدخل عن طريق آلية الإخطار، إذ لا يمكن أن تتحرك المحكمة الدستورية من تلقاء نفسها، فهي لا تملك سلطة الإخطار التلقائي أو ما يسمى بالإخطار الذاتي، وإنما تكون دائما بحاجة إلى جهة دستورية تحرك الرقابة على دستورية القوانين أمامها بواسطة آلية الإخطار أو تخطرها بشأن حدوث ونشوب خلافات بين السلطات الدستورية أو تطلب رأيها بشأن تفسير حكم أو عدة أحكام دستورية، إذ من دون آلية الاخطار تبقى المحكمة الدستورية مكتوفة الأيدي إزاء النصوص المخالفة للدستور أو الخلافات التي تنشب بين السلطات الدستورية. إن إدخال المؤسس الدستوري في التعديل الدستوري سنة 2020 التعديلات المذكورة بخصوص الرقابة على دستورية القوانين لا يمكن من خلالها الجزم بأن المحكمة الدستورية مؤسسة رقابية مغايرة عن المجلس الدستوري وإنما هذه التعديلات تندرج ذمن إصلاح نظام الرقابة على دستورية القوانين من أجل إحداث رقابة فعالة، إلا أننا لم نصل بعد إلى الرقابة القضائية على دستورية القوانين حتى تكون المحكمة الدستورية مغايرة للمجلس الدستوري. In order to exercise its constitutional powers, the Constitutional Court needs the intervention of some parties determined by the constitutional founder, and the intervention is through the notification mechanism, as the Constitutional Court cannot move on its own, as it does not have the authority to automatically notify or what is called self-notification, but rather it always needs to A constitutional body that monitors the constitutionality of laws before it through the notification mechanism, or notifies it regarding the occurrence and outbreak of disputes between the constitutional authorities, or requests its opinion regarding the interpretation of a provision or several constitutional provisions, as without the notification mechanism, the Constitutional Court remains passive in the face of texts that violate the constitution or disputes that arise between them. Constitutional powers. The inclusion of the constitutional institution in the constitutional amendment in 2020, the aforementioned amendments regarding oversight of the constitutionality of laws, cannot be said to be certain that the Constitutional Court is a different oversight institution than the Constitutional Council. Rather, these amendments fall within the framework of reforming the system of oversight of the constitutionality of laws in order to create effective oversight. However, we have not We have yet to reach judicial oversight of the constitutionality of laws until the Constitutional Court is different from the Constitutional Council
ماستر اداري